2019
DOI: 10.4103/ijnm.ijnm_152_18
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon emission computed tomography myocardial ischemia detection in high-risk asymptomatic patients: correlation with coronary calcium score and high-sensitivity C-reactive protein

Abstract: Background: The association between myocardial ischemia in high-risk patients with coronary calcium score (CCS) and high-sensitivity C-reactive protein (hs-CRP) is not well established. Aims: We evaluated the correlation between hs-CRP, CCS, and myocardial ischemia in asymptomatic high-risk patients without known coronary artery disease (CAD). Materials and Methods: We prospectively assessed 68 asymptomatic high-risk outpatients without known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Whether levels of inflammation may be related to the presence of myocardial ischemia in patients with symptoms suggestive of CAD is a matter of ongoing research. A limited number of studies have reported a significant positive association of inflammation with MPI SPECT ischemia findings, although not consistently [22,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether levels of inflammation may be related to the presence of myocardial ischemia in patients with symptoms suggestive of CAD is a matter of ongoing research. A limited number of studies have reported a significant positive association of inflammation with MPI SPECT ischemia findings, although not consistently [22,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a proportion of patients with an MPI study, hs-CRP predicted positive MPI results [23]. However, data about the association of CRP with MPI findings are limited [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%